2020
DOI: 10.3390/ijerph17072530
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Factors for the Relationship between Stress and Work Ability over Time in Young Adults

Abstract: Stress can affect work ability. The aim of this study was to identify how this pathway is mediated over time in young adults. Participants of the Work Ability in Young Adults cohort were selected. A theoretical framework was built, which lead to a statistical model. Selected dimensions of mediators were recovery, work demands affecting private life, feelings of control over private life, and physical activity in leisure time. A quadruple serial mediation model was built with four mediators. The total effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(68 reference statements)
1
1
0
Order By: Relevance
“…The reason being that Baron and Kenny ( 1986 ) mediation model remains very relevant for mediation analysis in this twenty-first century. For instance, van Schaaijk et al ( 2020 ) with Chen et al ( 2020 ) method of mediation analysis is consistent with this research use of Baron and Kenny ( 1986 ) mediation model.…”
Section: Validation Of Research Instrumentsupporting
confidence: 79%
“…The reason being that Baron and Kenny ( 1986 ) mediation model remains very relevant for mediation analysis in this twenty-first century. For instance, van Schaaijk et al ( 2020 ) with Chen et al ( 2020 ) method of mediation analysis is consistent with this research use of Baron and Kenny ( 1986 ) mediation model.…”
Section: Validation Of Research Instrumentsupporting
confidence: 79%
“…The investigation of the study of the direct relationship between the EI and COs confirmed that three out of five dimensions of EI (SA, SR, and SS) significantly influenced the COs, supporting our intuitions in the hypotheses H1.1, H1.2, and H1.5. The previous studies have shown that these skills have a significant positive relationship with the COs (Bentler and Bonett, 1980 ; Li, 2009 ; Van Schaaijk et al, 2020 ). Charoensukmongkol and Phungsoonthorn's ( 2020a ) research into the impact of EI on cognitive processes among University of Malaga undergraduates ( N = 178) concluded that the higher levels of EI were strongly predictive of COs.…”
Section: Discussionmentioning
confidence: 92%
“…The independent variable is sustainability, which includes three subfactors: social, environmental, and economic aspects. Similarly, the mediating variable is the one that helps in creating an association between dependent and independent variables that explores the relationship among the two variables (van Schaaijk et al 2020). It is mainly a hypothetical variable that acts as a mediator in the connecting of the two variables.…”
Section: Hypothesis Developmentmentioning
confidence: 99%